Ophthalmic manifestations of children with Down syndrome in Port Harcourt, Nigeria - Adio, Adedayo Omobolanle (Dove Medical Press, 2012)
AIM: The aim of this study was to provide a profile of oculo-visual anomalies in children with Down syndrome (DS) in Port Harcourt, Nigeria. METHODS: This comparative study assessed the visual functions of 120 children (42 DS and 78 developmentally normal children). The visual functions evaluated and the techniques used were: visual acuity (Snellen illiterate chart and Lea picture charts), refraction (static retinoscopy with cyclopegia), ocular alignment (cover test), near point of convergence (pen and rule), and external examinations and fundoscopy. RESULTS: A total of 42 children with DS (22 males, 20 females, mean age 11.43 ± 6.041 years) and control group of 78 normal children (36 females, 42 males) with mean age 6.63 ± 1.98 years were examined. Of the 42 DS children, visual acuity was less than 6/18 in eight and one of the DS and control groups, respectively. Visual acuity could not be checked conventionally in eleven participants from the DS group due to poor response. The main findings were: DS compared to control group showed refractive errors of 76.2% (half of which was from myopia) vs 14.1% (only 10% due to myopia). There was a statistically significant difference in total refractive errors between the Down syndrome group and the control group (P = 0.001, χ(2) = 18.29). Strabismus was 9.5% (75% esotropia) vs 0%, and there was a statistically significant difference (P = 0.001, χ(2) = 5.01), nystagmus was 4.8% v 0%, conjunctivitis 19.05% vs 8.97%, and keratitis 7.14% vs 0%, which was statistically significant (P = 0.05, χ(2) = 2.90). CONCLUSION: Refractive errors were prevalent in a sample of children with DS in Port Harcourt, Nigeria, whereas the prevalence of ocular diseases was low when compared to age-matched control participants. This study highlights the need for ophthalmic care in children with DS. Routine eye care such as the use of spectacles when necessary is recommended for people with DS at all ages to improve their educational and social needs as well as overall quality of life.